How to Save a Life - Douglas Ander; Katherine Heilpern (Association of American Medical Colleges, 2009)
Abstract Introduction Students should be able to institute lifesaving maneuvers effectively for airway compromise, lethal arrhythmias, or a choking patient. If these maneuvers cannot be instituted effectively, the patient will not survive past the first 4-6 minutes. At the Emory University School of Medicine, all third-year medical students receive a weeklong orientation prior to starting their clinical rotations. As part of the orientation, students are required to participate in this half-day course on how to save a life. Methods This resource consists of lectures and hands-on mannequin training. The main objective is to teach lifesaving techniques that would support a critically ill patient for the first several minutes of a cardiac or airway emergency. Content validity was established by a group of educators at the Emory University School of Medicine. Content is based on national life-support courses and internal expertise. Results Our initial work, published in the American Journal of Emergency Medicine as a letter, described improvements in student comfort with the skills. A more recent study was presented at the Society for Academic Emergency Medicine Annual Meeting in May 2006 showing that with the initial training, students were able to achieve 100% competency in the skills. We retested a subset of students approximately 18 months after the initial training and noted a decrease in competency, especially in recognition and treatment of ventricular fibrillation and pediatric choking. This was likely related to a lack of clinical experience demonstrated in the study. The resource contains a copy of the poster with these data. Discussion With 2 half-day sessions utilizing a total of 10 faculty each, we have been able to train 105 students. This allows us to have a 1:4-6 faculty:student ratio. Fewer faculty are need if the ratio is adjusted higher.